2017
DOI: 10.1038/s41598-017-15633-w
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management and Prognostic Prediction of Adenocarcinoma of Jejunum and Ileum

Abstract: We conducted a retrospective study based on the Surveillance, Epidemiology, and End Results Program (SEER) database to establish a novel nomogram prognostic prediction system and to estimate the association between overall survival and prognostic factors, as well as to explore surgical treatment strategies for adenocarcinoma of the jejunum and ileum. A total of 883 patients from the SEER database were included in this study. Eight potential prognostic factors were included in a nomogram model and discriminator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It has an approximate incidence of 2.4 per 100,000 inhabitants, an apparent predominance for black males and a median age at diagnosis of between 55 and 66 years old. 1,6 Of these types of tumors, only 13.2 to 31% of cases seem to affect the jejunum, with the duodenum acting as the main location in most patients (between 48 and 73.6% of cases). 3 For a long time, adenocarcinomas were the most common histological type of malignant neoplasm affecting the small bowel, with up to 45% of cases; nevertheless, over the last 2 decades, neuroendocrine tumors have increased their incidence, becoming the main type of small bowel cancer in current times (44% versus 33% of cases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has an approximate incidence of 2.4 per 100,000 inhabitants, an apparent predominance for black males and a median age at diagnosis of between 55 and 66 years old. 1,6 Of these types of tumors, only 13.2 to 31% of cases seem to affect the jejunum, with the duodenum acting as the main location in most patients (between 48 and 73.6% of cases). 3 For a long time, adenocarcinomas were the most common histological type of malignant neoplasm affecting the small bowel, with up to 45% of cases; nevertheless, over the last 2 decades, neuroendocrine tumors have increased their incidence, becoming the main type of small bowel cancer in current times (44% versus 33% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the study by Xie et al did not find significant differences in prognosis regarding gender, race, or intestinal location of the tumor. 6 Coronavirus disease 2019 is an infectious disease caused by the severe acute respiratory syndrome coronavirus 2, which has managed to become a global health issue, with an estimated 12,964,809 cases and 570,288 deaths reported to the WHO by mid-July. 4 While initially thought to only affect the airways, symptoms of organic affection became apparent as the number of cases increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data also demonstrate the complex nature of the surgery required for small bowel malignancies. This results from local invasion, the anatomy of the small intestine and its associated vasculature [3,29]. As a result, small bowel resection alone is seldom sufficient to achieve oncological clearance and, in the event, that small bowel resection alone is required, the length of bowel resected is often significant.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node invasion has been reported as the most significant prognostic factor [6,7]. Similar to the colorectal cancer setting, the number of lymph nodes that are retrieved and examined in the surgical specimen is also considered to offer prognostic value [9][10][11]. While the optimal extent of lymph node dissection in small bowel adenocarcinoma is unclear, a recently published study suggested that resection of at least 12 lymph nodes, akin to recommendations used for large bowel cancer, is likely to improve the survival in patients with jejunal and ileal adenocarcinomas [10].…”
Section: Introductionmentioning
confidence: 99%